Angiographic patency after robotic beating heart totally endoscopic coronary artery bypass grafting facilitated by automated distal anastomotic connectors. (9th October 2020) - Balkhy, Husam H; Nathan, Sandeep; Torregrossa, Gianluca; Kitahara, Hiroto; Nisivaco, Sarah; McCrorey, Mackenzie; Patel, Brooke
Abstract: OBJECTIVES: Robotic totally endoscopic coronary artery bypass (TECAB) on the beating heart has been facilitated in our experience using distal coronary anastomotic connectors. In this study, we retrospectively reviewed graft patency in all robotic TECAB patients who underwent formal angiography at our current institution over a 5-year period. METHODS: Between July 2013 and June 2018, 361 consecutive patients underwent robotic beating-heart TECAB. Of these patients, 121 had a follow-up angiogram, which assessed graft patency. Eighty-four patients had an angiogram as part of planned hybrid procedures and 37 patients underwent an unplanned angiogram for clinical indications. Retrospective analysis of angiographic patency and clinical outcomes was performed. RESULTS: The mean Society of Thoracic Surgeons predicted risk of mortality was 1.8%. Single-vessel bypass was performed in 40 (33%) patients and multivessel grafting in 81 (67%). Average flow (ml/min) and pulsatility index in the grafts was 74.7 ± 39.1 and 1.42 ± 0.52, respectively. The number of grafts evaluated was 204 (130 left internal mammary artery and 74 right internal mammary artery grafts). The median time to angiography was 1.0 and 16.0 months and graft patency was 98% and 91% in the hybrid and non-hybrid groups, respectively. Overall graft patency was 95.6% (left internal mammary artery = 96%; right internal mammary artery = 93%). Left internal mammary artery to left anterior descending artery graft patency was 97%. Clinical follow-up was available for 316 (88%) patients at mean 22.5 ± 15.1 months. Freedom from major adverse cardiac events at 2 years was 92%. CONCLUSIONS: In this consecutive series of patients undergoing formal angiography after robotic single and multivessel TECAB, we found satisfactory graft patency and 2-year clinical outcomes. Longer-term follow-up is warranted. Abstract : Robotic totally endoscopic beating-heart coronary bypass surgery, the least invasive form of coronary artery bypass grafting (CABG) surgery, has been shown to be safe and reproducible with an experienced surgical team in selected patients [1, 2].